Observations on the Flora of Dampa Tiger Reserve in Bio-Resource and Park Management Perspectives - Haridasan, K.; Bisht, N. S.; Paul, Martin; Suresh, Geetha (Indian Forester, 2016)
Dampa Tiger Reserve (DTR) in Mizoram is an important biodiversity spot in northeast India with rich vegetation and floristic diversity that are well preserved. A study of the flora here revealed that the DTR not only shelters a good number of threatened plants but also harbours a large pool of important species which are directly beneficial to the fauna. It supports substantial number of species capable of contributing to the livelihood and health security of the surrounding community too. A proper understanding of these species will help in effective implementation of the management plan for this protected area.